Kant, Baudelaire and the breakup of the Neoclassical ideal of human beauty - Tobón Giraldo, Daniel Jerónimo (Estudios de Filosofía, 2011)
In the realm of Contemporary Visual Arts, there hovers over Human Beauty a tacit ban. The Human Body is still one of the central themes of Art, but it is not in the habit of being represented as beautiful: emphasis is laid on its ugliness, or in the terrible or abject aspects of Corporality. This paper tries to understand the process that led to this situation starting from the transformation of the concept of “Ideal Beauty” between Kant and Baudelaire, which shows a deep connection between the concept of Human Beauty and the hope for Moral Progress. We maintain that the break-up of this hope is one of the reasons why Modern and Contemporary Art have rejected so forcefully the representation of Ideal Beauty.